ASSESSMENT AND ANALYSIS OF THE QALITY OF A SUPPORT SERVICE DONE FROM USERS' STANDPOINT: FIRST STEP FOR REALIABILITY - Pérez Rave, Jorge (2007)
The assessment and analysis of the technical support service's quality of the Engineering Department of the University of Antioquia(Colombia) is show in this article. The aforementioned methodology integrates elements of: qualitative research, multivariable statistics, quality, probability theory and system reliability. In the present article is discussed that, quality analysis should be seen as the first step for reliability analysis, which is more effective for firms because it allows them to know the behavior of quality throughout time, the flaws in their service, their improvement activities must be oriented.